HPV and Cardiovascular Risk: Unpacking a Novel Link Between Viral Infection and Heart Disease - Alisha Arzoo (International Journal of Virus Studies, 2025)
Human papillomavirus (HPV) is best known for its oncogenic potential, yet a growing body of evidence suggests that persistent HPV infection may also contribute to cardiovascular disease (CVD). In 2025, pooled analyses and conference reports galvanized attention by estimating that HPV‐positive individuals have ~40% higher risk of CVD and approximately double the risk of coronary artery disease (CAD) compared with HPV‐negative peers, even after adjustment for traditional risk factors. These findings build on earlier cohorts linking high‐risk HPV (hrHPV) to incident CVD and, more recently, to CVD mortality in population studies. Mechanistic hypotheses include chronic low‐grade inflammation, endothelial dysfunction, immune and metabolic reprogramming driven by HPV oncoproteins (E6/E7), and even more provocatively possible direct vascular involvement, with small studies detecting HPV DNA and proteins within atherosclerotic plaques. Although causality is not proven, the totality of data positions HPV as a candidate “non-traditional” risk factor that may help explain residual CVD risk beyond smoking, hypertension, dyslipidemia, and diabetes.This review synthesizes epidemiologic signals, pathophysiologic plausibility, and early translational observations connecting HPV to atherosclerotic disease and stroke. It also considers the emerging question of whether HPV vaccination might confer cardiometabolic spillover benefits. We highlight knowledge gaps (temporal dynamics, genotype specificity, sex differences, and confounding by sexual health and socioeconomic determinants), outline practical, low-regret clinical responses (opportunistic vaccination, vigilant risk factor control in hrHPV-positive adults), and propose a research agenda spanning prospective cohorts, plaque viromics, and randomized vaccine-outcome trials. While definitive causality awaits, clinicians and public health teams should recognize HPV as a potential contributor to CVD risk and leverage existing prevention tools particularly vaccination and aggressive management of modifiable riskswhile the science matures.
Keywords: Atherosclerosis; Cardiovascular disease; Coronary Artery Disease; Endothelial Dysfunction; HPV vaccination; Human papillomavirus; inflammation; residual risk